Transformacja systemowa edukacji - Denek, Kazimierz (Wydawnictwo Naukowe UAM w Poznaniu, 1999)
During the last two decades of the 20th century the Polish education system has not kept up with reforms which took place in the EC and the US. As a result, it found itself in a state of collapse. It insufficiently obeys such general principles of functioning of contemporary school system as: commonness, permeability, broad profile, flexibility and socialization of education. It is also hard to speak of adapting education to changes in demography, economics, technology, social life and culture, as well as it is hard to say that education supports democratization processes in Poland, or Polish integration with Western Europe. Thus, there is a need of a complex reform in these circumstances, the one which would cover structural and organizational issues, as well as the ones concerning curricula and methods. The author indicates attempts to solve the problems.
System transformation and education
Keywords: Koncepcja szkoły; Conception of school; Transformacja edukacji; Transformation of education; Szkoła; School; Edukacja; Education; Oświata; Learning